Entanglement entropy of non-Hermitian free fermions. (10th September 2021) - Guo, Yi-Bin; Yu, Yi-Cong; Huang, Rui-Zhen; Yang, Li-Ping; Chi, Run-Ze; Liao, Hai-Jun; Xiang, Tao
Abstract: We study the entanglement properties of non-Hermitian free fermionic models with translation symmetry using the correlation matrix technique. Our results show that the entanglement entropy has a logarithmic correction to the area law in both one-dimensional and two-dimensional systems. For any one-dimensional one-band system, we prove that each Fermi point of the system contributes exactly 1/2 to the coefficient c of the logarithmic correction. Moreover, this relation between c and Fermi point is verified for more general one-dimensional and two-dimensional cases by numerical calculations and finite-size scaling analysis. In addition, we also study the single-particle and density–density correlation functions.